PENGUJIAN STABILITAS STRUKTURAL PENGARUH GROWTH POTENTIAL, EARNINGS VARIABILITY, TAX SHIELDS, FIRM SIZE DAN PROFITABILITY TERHADAP LEVERAGE RATIO PERUSAHAAN TEKSTIL DAN GARMEN DI BURSA EFEK JAKARTA SEBELUM DAN SELAMA KRISIS EKONOMI - Kristyana Dananti; Magdalena Nany (Jurnal Riset Manajemen dan Bisnis, 2007)
This research was intended to examine the structural stability of the fficts of growth potential, earnings variability, tax shields, firm size and profitability on leverage ratio in textile and garment companies at Jakarta Stock Exchange before and during the monetary crisis. Sixteen textile and garment companies were analyze using the Chow Test. The results show that there is a dffirence between the fficts of growth potential, earnings variability, tax shields, fir* size and profitability on leverage ratio before the monetary crisis and during the monetary crisis.Keywords: capital structure, growth potential, earnings variability, tm shields, -fir* size, profitability, leverage ratio, monetary crisis